2017
DOI: 10.1177/1093526617745431
|View full text |Cite|
|
Sign up to set email alerts
|

Solitary Fibrous Tumors in Pediatric Patients: A Rare and Potentially Overdiagnosed Neoplasm, Confirmed by STAT6 Immunohistochemistry

Abstract: Pathological diagnosis of solitary fibrous tumor (SFT) in the pediatric population is challenging, as it occurs uncommonly in this age-group and resembles other spindle cell neoplasms. SFT contains a NAB2-STAT6 fusion gene, which can be reliably detected using STAT6 immunohistochemistry. Positive staining is highly sensitive and specific. We sought to investigate the utility of STAT6 immunohistochemistry, to show how commonly SFT was historically recognized at 3 academic pediatric institutions, to reclassify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…6 Tan et al examined 30 years of archives from 3 pediatric hospitals and identified 18 solitary fibrous tumor diagnoses. 9 Of the 18 tumors, only 3 tumors from 2 patients demonstrated positive STAT6 staining and the typical histology and immunophenotype of solitary fibrous tumors. The remaining 15 tumors were reclassified as other types of soft tissue tumors after application of STAT6 immunohistochemistry, highlighting the rarity of solitary fibrous tumors in children and the importance of STAT6 as the diagnostic marker.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…6 Tan et al examined 30 years of archives from 3 pediatric hospitals and identified 18 solitary fibrous tumor diagnoses. 9 Of the 18 tumors, only 3 tumors from 2 patients demonstrated positive STAT6 staining and the typical histology and immunophenotype of solitary fibrous tumors. The remaining 15 tumors were reclassified as other types of soft tissue tumors after application of STAT6 immunohistochemistry, highlighting the rarity of solitary fibrous tumors in children and the importance of STAT6 as the diagnostic marker.…”
Section: Discussionmentioning
confidence: 93%
“…5 Solitary fibrous tumors have been reported to show immunoreactivity for CD34, Bcl-2, and CD99. 9 The discovery of gene fusion between NAB2 and STAT6 that leads to the upregulation of STAT6, a novel immunohistochemical marker, has been shown to be of diagnostic importance in these tumors. 6 Tan et al examined 30 years of archives from 3 pediatric hospitals and identified 18 solitary fibrous tumor diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary adenofibroma (PAF) is the most frequent and the most striking and misleading pattern Table 2 Entrapment of alveolar/respiratory epithelium in different primary and metastatic pulmonary lesions [6]. Following discovery of STAT6-NAB2 gene fusions as driver events in most of SFTs, STAT6 IHC has emerged as highly sensitive and specific marker for SFT [7][8][9]. In the pre-STAT6 era however, many PAF-like SFTs were misclassified as PAF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study[ 24 ] from three pediatric hospitals reevaluating prior pathology from the past 30 years found that 18 tumors total were classified as SFTs. However, when immunohistochemistry was performed on the tissue, only three tumors from two patients were found to be STAT6 positive; the remainder tumors required reclassification.…”
Section: Discussionmentioning
confidence: 99%